Implementation Of Sem Model: Combination Of Tam And Tpb In Using Onshore Power Supply In Ports Of Java Island - Indonesia - Febriyanti Febriyanti; Muhammad Thamrin; Lira Agusinta; Yosi Pahala (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the influence of variables within the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) on behavioral intention and actual use of Onshore Power Supply (OPS) in Java Island ports, Indonesia. The study employs a quantitative approach with seven constructs: Perceived Ease of Use, Perceived Usefulness, Perceived Risk, Subjective Norm, Attitude Toward Using OPS, Behavioral Intention to Use OPS, and Actual System Use of OPS. The novelty of this research lies in the application of a combined TAM and TPB model to analyze OPS adoption in ports as a strategic step to support environmental sustainability and operational efficiency. Data collection involved a Likert-scale (1-5) questionnaire distributed to 240 OPS users across various ports on Java Island and interviewed with 10 informants from both operators and users. The data were analyzed using the Structural Equation Modeling (SEM) approach with PLS version 4.0.9.6. The results of testing 14 hypotheses show that all variables have a positive and significant influence on behavioral intention and actual use of OPS, with Subjective Norm being the most significant contributor to Attitude Toward Using OPS (coefficient value of 0.378). The study also revealed that the lowest-rated indicators were related to the perceived ease of approval processes for OPS construction (Perceived Ease of Use), user comfort (Perceived Usefulness), and perceived risks of equipment damage (Perceived Risk). To address these issues, strategic steps such as digitizing licensing processes, automating OPS systems, and implementing international safety standards are recommended. The proposed policy implications involve the government providing incentives for environmentally friendly technologies and enabling regulations to strengthen the adoption of OPS in national ports. This research significantly contributes to the development of policies and operational strategies that support the transition of ports in Indonesia toward more sustainable and environmentally efficient practices.